Anesthesia management of laser photocoagulation for retinopathy of prematurity. A retrospective review of perioperative adverse events. Issue 11 (13th September 2020) - Kaur, Balvindar; Carden, Susan M.; Wong, Jonathan; Frawley, Geoff
Abstract: Aims: The aim of this study was to report the incidence of perioperative adverse events occurring in infants undergoing diode laser photocoagulation of retinopathy of prematurity and to identify clinical risk factors that may affect the incidence. Methods: This was a retrospective study of anesthetic and medical records of premature infants who were treated in the neonatal intensive care unit or an operating theater with laser photocoagulation in our institution between January 2014 and December 2019. Infants less than 38 weeks post‐menstrual age or less than 2000 grams were considered high risk for complications. Electronic medical records were evaluated for clinical and demographic characteristics, comorbidities, and perioperative complications of anesthesia. Results: Sixty‐one infants (39 males, 22 females) underwent 72 laser treatments. The mean gestational age was 25.3 weeks (SD 1.6), and mean birth weight was 730 grams (SD 202). At treatment, the mean postmenstrual age was 37.5 weeks (SD 2.7) and weight was 2320 g (SD 610). Laser therapy was performed in an operating theater in 66 procedures (91.7%) and in the neonatal unit in 6 cases (8.3%). Twenty‐nine (40.3%) laser surgeries occurred outside normal week‐day daytime operating hours. Intraoperative hypotension occurred in 12 procedures (16.7%) but was not significantly different in high‐risk infants (16.1% vs 16.7% OR 0.94 P  = .94) or in procedures performed in‐hours (16.3% vs 17.2% OR 0.93 P  = .91). Post‐extubation apnea occurred in 21 procedures (29%) but was not significantly different in high‐risk infants (29.0% vs 27.3% OR 0.98 P  = .34) or in procedures performed in‐hours (27.9% vs 31.1% OR 0.86 P  = .77). Infants remained intubated at the end of the procedure in 58 (80.5%) cases and 29 (40.3%) remained ventilated more than 24 hours after the procedure. Conclusion: The incidence of perioperative adverse events was not associated with patient's age, current weight, timing, or location of the procedure. Extubating infants at the end of the procedure is however associated with a high rate of apneas and bradycardia, and consideration should be given to keeping low weight infants undergoing prolonged procedures out‐of‐hours intubated.